The Effect of Work-Family Conflict and Social Support on Job Satisfaction: A Case Study of Female Employees in Indonesia - Asbari, Masduki; Purwanto, Agus; Sudargini, Yuli; Fahmi, Khaerul (IJOSMAS, 2020)
This study aimed to measure the effect of work-family conflict and social support (supervisor, peer, and family support) on the job satisfaction of the female employees of two private companies in Indonesia. Data collection was done by simple random sampling of 145 population of female employees. The returned and valid questionnaire results were 139 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that work-family conflict, peer support, and family support have a significant effect on job satisfaction. Meanwhile, supervisor support has not a significant effect on job satisfaction. This new research proposed a model for building job satisfaction among the private company employees in Indonesia through enhancing social support and manage work-family conflict.